2017
DOI: 10.1515/reveh-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Status of water pollution in relation to industrialization in Rajasthan

Abstract: AbstractIndia is a large and densely populated country; its economy is largely agricultural. Making the best use of the country’s manpower has always posed a challenge. Industrialization could become a dominant component of the economy and displace agriculture. Traditional livelihoods of occupational groups are threatened by the practice of disposing untreated industrial waste into rivers and bodies of water. These uncontrolled disposals impact local natural resources with nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The absence of absorption land causes river water to be exposed to pollution runoff from agricultural land (Juma et al, 2014). Household and industrial waste that is dumped directly into rivers is another cause of declining water quality (Rajput et al, 2017). The evidence from Kido et al (2009) showed lack of drainage system in developing countries includes Indonesia causes industrial, agricultural and domestics water is directly discarded into rivers.…”
Section: Acceptedmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of absorption land causes river water to be exposed to pollution runoff from agricultural land (Juma et al, 2014). Household and industrial waste that is dumped directly into rivers is another cause of declining water quality (Rajput et al, 2017). The evidence from Kido et al (2009) showed lack of drainage system in developing countries includes Indonesia causes industrial, agricultural and domestics water is directly discarded into rivers.…”
Section: Acceptedmentioning
confidence: 99%
“…The population growth and economic growth also drive the growth of waste. A study showed that untreated waste that directly dropped into river or waterway cause water pollution (Rajput, Pandey, Bhadauria, & India, 2017). In summary, it can be concluded that environmental quality is affected by economic growth and population (POP).…”
Section: Introductionmentioning
confidence: 99%
“…The demand for fi sh and the consumption rate is increasing gradually. It has an urgent requirement for the fi sh market development in the rural part of India [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of such materials with biodegradable or biocompatible ones is the most attractive yet simple strategy and has received much attention in the last few years. [9][10][11] Graphene oxide (GO), a derivative of graphene, is in use for about one and a half centuries. It is a two dimensional (2-D) covalently bonded and oxygen-rich carbon skeletal.…”
Section: Introductionmentioning
confidence: 99%